2D oxides on metal materials: concepts, status, and perspectives. Issue 22 (22nd May 2019) - Barcaro, Giovanni; Fortunelli, Alessandro
Abstract : Two-dimensional oxide-on-metal materials: concepts, methods, and link to technological applications, with 5 subtopics: structural motifs, robustness, catalysis, ternaries, and nanopatterning. Abstract : Oxide materials at the two-dimensional limit, in particular in the form of ultrathin films of oxides (UTOx) grown on metal surfaces, represent promising materials in view of both fundamental science and technological applications. While the former aspect is widely recognized, these systems have not yet realized their full potential in terms of the latter (technological) aspect. In the present perspective, we review the field and its basic underlying concepts, and at the same time we provide an overview of the most promising future directions with a focus on their potential toward and relationships with real-world exploitation.